For love of magic - Green, Simon R., 1955- (Baen Publishing Enterprises, 2023)
"History can change and has changed. Magic was and is real. Once upon a time, there was a forgotten era of magic and monster. But the remnants-and all memory-of the old world have been replaced by the sane, the scientific, and the rational. But sometimes the magical past isn't content to stay past. That's where Jack Damian comes in. It's his joy to protect our present from the supernatural remnants of an earlier time, a different history. It's his job to make the past safe. Jack is called to the Tate Museum, where dozens of people have disappeared beneath the surface of a painting. While investigating, he finds himself smitten with a mysterious art expert Amanda Fielding. But Amanda has plans of her own, and soon the two are traveling through time - back to the Roman Empire and then forward through history, from King Arthur's court to Sherwood Forest. As they explore histories past as written and overwritten, the balance of magic and science shifts, and the choices the two make could change the world forever"--